Disinfection By-products in Drinking Water : Detection and Treatment - Prasad, M. N. V. (Majeti Narasimha Vara), 1953-, editor 323838; ScienceDirect (Online service) 7722 (London : Butterworth-Heinemann, 2020)
Disinfection Byproducts in Drinking Water: Detection and Treatment presents cutting-edge research on how to understand the procedures, processes and considerations for detecting and treating disinfection by-products from drinking water, swimming pool water, and wastewater. The book begins with an overview of the different groups of Disinfection Byproducts (DBPs), such as: Trihalomethanes (THM), Halo acetic acids, and Haloacetonitrile (HAN). This coverage is quickly followed by a clear and rigorous exposition of the latest methods and technologies for the characterization, occurrence, formation, transformation and removal of DBPs in drinking water. Other chapters focus on ultraviolet-visible spectroscopy, electron spin resonance, and gas chromatography-mass spectrometry.